INCREASED ADOPTION OF APPLICATION-BASED AGRIBUSINESS INFORMATION SYSTEM INNOVATIONS IN KAMPUNG HIDROPONIK GANG HIJAU ASMAT, SOUTH JAKARTA - Lilis Imamah Ichdayati; Dewi Rohma Wati; Noeramala Arkana (Syarif Hidayatullah State Islamic University Jakarta, 2021)
This research was backgrounded by urban communities the formed farmer groups to meet the needs of vegetable consumption in residential areas by utilizing the walls and fences of houses to increase green space, reduce air pollution, and increase income. Vegetables grown are sold in person or online. Agricultural extension is also not optimal, so it is necessary to adopt innovative agribusiness information systems such as the Farmer Application support. This study aims to, 1) Identify the characteristics of farmers in the Asmat Green Gang Hydroponic Village; 2) Analyze the relationship between farmer characteristics and the level of knowledge and the level of adoption of agribusiness information systems based on farmer applications; (3) Analyze the level of knowledge and perception of farmers with the level of adoption of agribusiness information systems based on farmer applications.The results of this study show that farmers in the Gang Hijau Asmat Hydroponic Village have not accepted or refused to apply the farmer application to their hydroponic vegetable farming business. This is because the socioeconomic characteristics of farmers are not related to the level of knowledge and adoption even though farmers' perceptions of farmer applications are good. Farmers there are classified as new farmers because they only started planting in 2017. They are also new to the Farmer application so that is still in the adjustment stage from what was originally direct counseling to online counseling. Farmers in This Hydroponic Village are included in the classification of early adopters to determine the speed at which farmers apply farmer applications.